Analysis of the crushing behaviors of woven carbon fiber reinforced plastic hat section component under dynamic bending and axial crushing loading. (April 2021) - Zhou, Guowei; Tang, Haibin; Sun, Qingping; Li, Dayong; Peng, Yinghong; Zeng, Danielle; Su, Xuming
Abstract: In current work, the crashworthiness of woven carbon fiber reinforced plastic (CFRP) hat section component is investigated under two types of loading experimentally and numerically, i.e., axial crushing and dynamic three-point bending. The crushing characteristics of woven CFRP hat section sample are evaluated at various impact velocities and layup orientations which exhibit different effects under two types of loading. With impact velocity/energy increasing, the bending behaviors illustrate different evolutions with distinct stages which are affected by the damage development. Layup orientation shows a little effect on the bending behaviors, while it exerts remarkable effects on the axial crushing which leads to different crushing modes and thus different energy absorption capabilities. The finite element model with multiple layers of thick shell element and cohesive element is shown to capture the crushing behaviors reasonably well in both axial crushing and dynamic bending. The corresponding damage evolutions are also analyzed with simulations to explain the crushing behaviors. Highlights: Crushing characteristics of woven CFRP hat section component are explored under dynamic bending and axial crushing. Crushing processes at different conditions are studied by high speed camera and ultrasonic scan. A finite element model is established to analyze the damage evolutions in two types of crushing.